2008
DOI: 10.1093/nar/gkn403
|View full text |Cite
|
Sign up to set email alerts
|

PARP inhibition versus PARP-1 silencing: different outcomes in terms of single-strand break repair and radiation susceptibility

Abstract: The consequences of PARP-1 disruption or inhibition on DNA single-strand break repair (SSBR) and radio-induced lethality were determined in synchronized, isogenic HeLa cells stably silenced or not for poly(ADP-ribose) polymerase-1 (PARP-1) (PARP-1KD) or XRCC1 (XRCC1KD). PARP-1 inhibition prevented XRCC1-YFP recruitment at sites of 405 nm laser micro irradiation, slowed SSBR 10-fold and triggered the accumulation of large persistent foci of GFP-PARP-1 and GFP-PCNA at photo damaged sites. These aggregates are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
163
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(195 citation statements)
references
References 53 publications
27
163
2
1
Order By: Relevance
“…Based on in vitro experimental evidence, 14,15 it has been suggested that the greatest therapeutic benefit a PARP inhibitor combined with radiotherapy would be seen in cells that are rapidly dividing as the greatest relative impact on cell killing from this combined treatment was seen in S-phase cells. In order to investigate whether transcript levels were modulated under these circumstances, we studied their correlation with the transcript level of the nuclear proliferative marker MKI67.…”
Section: Tumors While Those Tumors Having An Underexpression Have Thementioning
confidence: 99%
“…Based on in vitro experimental evidence, 14,15 it has been suggested that the greatest therapeutic benefit a PARP inhibitor combined with radiotherapy would be seen in cells that are rapidly dividing as the greatest relative impact on cell killing from this combined treatment was seen in S-phase cells. In order to investigate whether transcript levels were modulated under these circumstances, we studied their correlation with the transcript level of the nuclear proliferative marker MKI67.…”
Section: Tumors While Those Tumors Having An Underexpression Have Thementioning
confidence: 99%
“…Additionally, it has been shown that PARP-1 -/-knockout mice are more sensitive to radiation than wildtype mice [102]. In addition to knockout mice, studies examining the effect of PARP silencing using RNA interference have been effective in reduction of PARP and PARP activity and have increased radiosensitivity in a manner equivalent to PARP-1 -/-knockout mice [103]. In our hands, silencing of PARP-1 in glioblastoma cell lines was generally not as effective as treatment with a PARP inhibitor [104].…”
Section: Inhibitors Versus Deletion or Silencingmentioning
confidence: 99%
“…Next, we evaluated the effects of PARP inhibition on the ability of cancer cells to repair DNA SSBs, which are the most common type of DNA damage and are primarily repaired by base excision repair, a process catalyzed by PARP-1 through the formation of (PAR) chains (32)(33)(34)(35). It has previously been shown that the use of PARP inhibition leads to the accumulation of SSBs (12,36). We looked to evaluate whether the use of PARPi would lead to an increase in SSBs in JHU006 and JHU012 HNSCC cell lines.…”
Section: Parp Inhibition Induces Ssbs In Hnscc Cell Linesmentioning
confidence: 99%